Across the stages: a multiscale extension of the generalized stochastic microdosimetric model (MS-GSM2) to include the ultra-high dose rate - Battestini, Marco; Missiaggia, Marta; Attili, Andrea; Tommasino, Francesco; La Tessa, Chiara; Cordoni, Francesco G.; Scifoni, Emanuele (Frontiers in Physics, 2023)
Ultra-High Dose Rate (UHDR) irradiations with different types of radiation have shown a larger sparing of normal tissue and unchanged tumor control with respect to conventional delivery.Recent years have been characterized by an accumulation of experimental evidence regarding socalled FLASH effect. However, the underpinning mechanism remains to date extremely debated and largely unexplained, while the involvement of multiple scales of radiation damage has been suggested. Since it is believed that the chemical environment plays a crucial role in the FLASH effect, the aim of this work is developing a multi-stage tool, the Multiscale Generalized Stochastic Microdosimetric Model (MS-GSM2), that is able to capture several possible effects on DNA damage at UHDR regime, such as reduction of DNA damage yield thanks to radical recombination, damage fixation due to oxygenation, and spatial and temporal dose deposition effects, allowing to explore most of the candidate mechanisms for explaining the FLASH effect. The GSM2 is a probabilistic model that describes the time evolution of the DNA damages in a cell nucleus from microdosimetric principles, accounting for different levels of spatio-temporal stochasticity. In this work, we extend the GSM2 , coupling the evolution of DNA damages to fast chemical reaction kinetics, described by a system of ordinary differential equations, accounting for an additional level of stochasticity, in chemistry. We simulate energy deposition by particles in a microscopic volume, which mimics the cell nucleus, in order to examine the combined effects of several chemical species and the time evolution of DNA damage. We assume that UHDR modifies the time evolution of the peroxyl radical concentration, with a consequent reduction in the yield of the indirect DNA damage. This damage reduction emerges only at UHDR and is more pronounced at high doses. Moreover, the indirect damage yield reduction depends on the radiation quality.We show that MS-GSM2 can describe the empirical trend of dose and dose rate-dependent cell sensitivity over a broad range, particularly the larger sparing of healthy tissue occurring at the FLASH regime. The complete generality of MS-GSM2 allows also to study the impact of different dose delivery time structures and radiation qualities, including high-LET beams.